Experimental investigation on chemical clogging mechanism of loose porous media in recharge process of groundwater heat pump - Yang, Jie (Environmental technology, 2023)
Groundwater heat pumps (GWHP) are an efficient utilisation of shallow geothermal energy technology and of great significance in terms of promoting energy conservation and reducing emissions. However, recharge clogging has been a key problem restricting the continuous operation of GWHP. In this study, a simulation test device for sand column was designed with the aim of addressing chemical clogging induced by heat pump reinjection in a porous saline aquifer in the Huaibei Plain, China. The trend in the variation of the permeability coefficient was studied based on the detection of the sand sample composition, recharge water quality, and sand layer temperature, and the cause of formation was analysed using the saturation index (SI) and ion ratio method. The results indicated that the permeability coefficient in the sand column decreased exponentially, with a maximum and minimum decrease of 8.14% and 71.65% of the original coefficient, respectively, found in sections P2-P3 and P8-P9. Therefore, the clogging effect of the aquifer at approximately 200-400 mm from the recharge well was significant. Water-rock interactions predominantly involved the dissolution of halite, albite, chlorite, anhydrite, and dolomite and the precipitation of calcite, as well as the exchange adsorption of Ca2+ and Mg2+ to Na+, which were the key sources of ions during the water chemical evolution process. Finally, quartz was formed by the weathering and dissolution of aluminosilicate minerals such as albite, and particle migration and precipitation during the hydrodynamic disturbance were the primary causes of the front-end blockage of the column